A242 THE P2 ISOFORM CLASS OF THE TRANSCRIPTION FACTOR HNF4A PLAYS DNA REPAIR ROLE IN COLORECTAL CANCER. (1st March 2018) - Wilson, S; Babeu, J; Boisvert, F; Boudreau, F
Abstract: Background: In Canada, cancers of the colon and rectum are among the deadliest forms of the disease. Colorectal carcinomas typically feature an abnormal regulation of the transcription factor HNF4α. The HNF4A encoding gene gives rise to two isoform classes, P1- and P2-HNF4α, that have opposing roles in colorectal cancer. The latter, P2-HNF4α, promotes cell proliferation and is upregulated in many instances of colorectal cancer when compared to P1-HNF4α. Despite this, the functional role that P2-HNF4α plays in the phenotype of colorectal cancer is unknown. Aims: The goal of this research was to elucidate the functional role of P2-HNF4α in colorectal cancer by the identification of its protein cofactors in colorectal cancer cell lines. Methods: We chose a representative member of the P2-HNF4α class, HNF4α8, to overexpress in 293T and HCT116 cells. The cofactors of P2-HNF4α were identified by two separate co-immunoprecipitation techniques, GFP-Trap and BioID, coupled to quantitative mass spectrometry. Following induced genotoxic stress, P2-HNF4α's cofactors were identified anew by GFP-Trap and HNF4α's nuclear localization was visualized by immunofluorescence. Results: In total, 1066 proteins were identified, by BioID or GFP-Trap, as cofactors of P2-HNF4α. Through BioID, 1007 cofactors of P2-HNF4α were identified in the 293T and HCT116 cell lines, and 59 cofactors were identified in the 293T cell line through GFP-Trap. The two co-immunoprecipitation assays had 31 mutual cofactors, and several of these cofactors shared 'DNA repair' as common gene ontology. Many common targets are known to be involved in DNA repair and are also known to be involved in cancer, including TP53, NPM1, RAD50, and MCM3/4. Following genotoxic stress, induced by micro-irradiation or etoposide, the relationship between DNA repair and P2-HNF4α was further tested. Immunofluorescence revealed that HNF4α colocalizes to DNA damage loci (p-H2A.X) in the nucleus of HT-29 and Caco-2/15 colorectal cancerous cell lines. Conclusions: The functional role of P2-HNF4α in colorectal cancer could be clarified by the isoforms class' association with DNA repair proteins. These cofactors suggest a DNA repair activity for P2-HNF4α. Furthermore, HNF4α's involvement in DNA repair represents the prospect of a previously undescribed non-transcriptional role for the transcription factor. This link between the transcription factor and DNA repair proteins could become exploitable for therapeutic remedy of colorectal cancer thanks to the manipulability of P2-HNF4α as a ligand-binding nuclear factor. Funding Agencies: CAG, CIHR